Circular microalgal processes: From olive industry waste biorefinery to bioplastic degradation - Nicodemou, Andonia (My University, 2024)
Five microalgae strains, namely Isochrysis galbana, Microchloropsis gaditana, Scenedesmus obliquus, Nannochloropsis oculata and Tetraselmis suecica, were selected as potential candidates for polyunsaturated fatty acids’ (PUFAs) production, evaluating biomass productivity and their capacity to accumulate high lipid contents under different trophic modes. The results demonstrate that S. obliquus performed the highest biomass productivity that reached 0.13 and 0.14 g L-1 d-1 under mixotrophic and heterotrophic conditions, respectively. The production of lipids was maximal for I. galbana in mixotrophy and S. obliquus in heterotrophy, performing lipid productivities of 24.8 and 22.8 mg L-1 d-1, respectively. The most abundant saturated acid detected for all microalgae strains evaluated was palmitic acid (C16:0), while oleic and linolenic acids (C18:1n9c/C18:3n3) comprised the most abundant unsaturated fatty acids. I. galbana performed the highest linoleic acid (C18:2n6c) content under heterotrophic nutrition, which reached 87.9 mg g-1 of ash-free dry weight. Among the microalgae strains compared, the biomass and lipid production monitored for I. galbana and S. obliquus confirm that both strains could serve as efficient bioproducers for application in algal biorefineries. Thus, a biorefinery was developed employing olive pomace (OP) and table olive processing wastewater (TOPW) for the manufacture of polyphenols, lipids and algal biomass. Hydrolysis of 100 kg exhausted OP (EOP) performed under the most efficient conditions yielded release of 54.5 kg of sugars and 3.2 kg of polyphenols. Application of XAD16N and PAD900 resins exhibited the highest overall polyphenols recovery, that reached 79.5% and 58.0% for TOPW and EOP extracts respectively. The hydrolysates generated following polyphenols recovery were evaluated as feedstocks for lipids production by S. obliquus and I. galbana, demonstrating maximum biomass and lipid productivity that reached 190 mg L-1 d-1 and 61.4 mg L-1 d-1 for S. obliquus, as well as 32 mg L-1 d-1 and 8.4 mg L-1 d-1 for I. galbana respectively. The results confirmed that both strains could serve as advanced bioproducers of PUFAs in microalgal biorefineries. Subsequently, the study enhanced S. obliquus cultivation via optimization of C/N (carbon/nitrogen) and C/P (carbon/phosphorus) ratios in synthetic media and evaluated a two-stage cultivation strategy through application of salinity stress in olive processing wastewater-based feedstocks. S. obliquus under 40/1 C/N ratio performed biomass and lipid productivity that reached 0.15 and 34.1 mg L-1 d-1 respectively, demonstrating high glucose removal efficiency. Application of a two-stage cultivation strategy employing 0, 10, 20 and 30 g L-1 NaCl during the second bioprocess segment resulted in elevated biomass productivity (0.14–0.19 g L-1 d-1), which was reduced under batch mode yielding 0.11 g L-1 d-1. Two-stage cultivation triggered higher lipid productivity (4.2%-156.9%) following 3 d and 6 d upon the onset of the second stage (42.7–55.2 mg L-1 d-1) as compared to batch conditions. Proline, glycerol and reactive oxygen species accumulated at considerable levels employing 20 and 30 g L-1 NaCl, indicating that S. obliquus expressed cellular stress under elevated salinity content, which was not notably stimulated using 10 g L-1 NaCl. The use of olive processing wastewater in a two-stage cultivation strategy under stress conditions enables future development of algal biorefinery systems for production of S. obliquus biomass and PUFAs as high added-value products from biowaste. The study also investigated the ability of S. obliquus to biodegrade poly-3-hydroxybutyrate (PHB) and thermoplastic starch (TPS) pellets under autotrophic and mixotrophic conditions, with and without air and CO₂ supplementation. In mixotrophic cultures without air, PHB and TPS weight decreased by 5.8% and 9.8%, respectively, while TPS weight was reduced by 8.7-9.9% under autotrophic conditions. Fatty acid profiles and organic carbon removal in mixotrophic cultures suggest potential for biodiesel production and environmental remediation. Microplastics generation was lower in mixotrophic (1-21 particles μL-1) than autotrophic (86-209 particles μL-1) conditions. Moreover, attenuated total reflectance profiles showed reduced peak intensities for both PHB and TPS, aligning with bioplastics’ weight loss. Overall, S. obliquus demonstrated a higher capacity to degrade TPS than PHB, with both autotrophic and mixotrophic conditions showing similar extents of biodegradation. This study highlights S. obliquus’s potential for bioplastics degradation, valuable bioproduct generation, and environmental remediation.
Keywords: Microalgae; Olive industry processing waste; Polyphenols; Polyunsaturated fatty acids; Biorefinery; Bioplastics